Effect of Addition Titanium Dioxide Nanoparticle on Properties of Pineapple Leaf Fiber Mediated TEMPO Oxidation Oxidation - Suryanto, Heru; Fikri, Ahmad Atif; Aminnudin, Aminnudin; Maulana, Jibril; Fadillah, Faqih; Mito, Mohamed T; Masera, Kemal; Ramadhan, Rahmad Ikrom (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Indonesia is an agricultural country with the potential to grow many plants as natural fiber sources. In order to improve its properties, natural fiber needs to be treated by applying nanomaterial so that it can compete with the characteristics of synthetic fibers. The study aims to determine the influence of adding titanium dioxide (TiO2) nanoparticles on pineapple leaf fiber (PALF) characteristics. The PALF was collected from the Subang plantation (Indonesia). The chemical treatment was carried out with pre-treatment using an alkalization process for 3 hours, and the oxidation process was carried out with TEMPO. TiO2 nanoparticle grafting was carried out by adding a silane solution with a ratio of 1:10 with alcohol. The characteristics of PALF were observed using XRD, FTIR, SEM, and tensile tests. The results show that the crystallinity of the PALF increased after TEMPO treatment. PALF form Si-O-C bond identified at a wavelength of 1158 cm-1 after silane treatment. Ti – O – Si functional groups were identified in the 660 cm-1 – 670 cm-1 wavelength range. In the fiber surface, agglomerated TiO2 nanoparticles are formed and increase with increasing TiO2 nanoparticle concentration. The tensile stress of treated PALF is increased by 125%, with the highest tensile strength of 1279.18 MPa, obtained by TiO2 nanoparticle concentration of 1.0%.